Additional measures of National Antarctic Scientific Center for the ensuring of the environment protection at Vernadsky station - Lytvynov, V.; Kuzko, O.; Bouraou, N.; Protasov, A.; Kyrychuk, O. (Ukrainian Antarctic Journal, 2009)
In addition to the generally accepted constructive solutions in Antarctica to prevent fuel leakages from the fuel tank the development and the mounting are proposed of the automated control system of the tank functional state for the early warning of possible fuel leakages. Such automatic system for control of the fuel tank functional state under the Antarctic conditions is proposed for the first time.